2019
DOI: 10.5334/aogh.2633
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Aid Allocation: Analysis of Official Development Spending on Modern Pollution Reduction

Abstract: Background:Modern pollution – pollution attributable to industrialization and urbanization – is responsible for nearly 6 million deaths per year, more than all the deaths from HIV, malaria, and tuberculosis combined; yet it receives comparatively little attention in the international development agenda [1].Objective/Methods:This study attempts to highlight the funding disparity between select key threats to global health by quantifying the levels of international official development aid (ODA) allocated to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…An analysis of available OECD figures for 2016 on official development assistance (ODA) concluded that donor countries have not responded to the global crisis of pollutionrelated disease and death through expanded investment in pollution control. 66 A 2019 study of ODA from bilateral and UN agencies allocated to reducing modern pollution found that support fluctuated from year to year and that there was no overall upward trend. 66 ODA contributions to international conventions and frame works concerning pollutants and chemicals amounted to $860 million in 2016-18, which is inadequate for the size and scope of the problem.…”
Section: Mobilise Increase and Focus Funding And International Techni...mentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of available OECD figures for 2016 on official development assistance (ODA) concluded that donor countries have not responded to the global crisis of pollutionrelated disease and death through expanded investment in pollution control. 66 A 2019 study of ODA from bilateral and UN agencies allocated to reducing modern pollution found that support fluctuated from year to year and that there was no overall upward trend. 66 ODA contributions to international conventions and frame works concerning pollutants and chemicals amounted to $860 million in 2016-18, which is inadequate for the size and scope of the problem.…”
Section: Mobilise Increase and Focus Funding And International Techni...mentioning
confidence: 99%
“…66 A 2019 study of ODA from bilateral and UN agencies allocated to reducing modern pollution found that support fluctuated from year to year and that there was no overall upward trend. 66 ODA contributions to international conventions and frame works concerning pollutants and chemicals amounted to $860 million in 2016-18, which is inadequate for the size and scope of the problem. Private philanthropic funding for pollution control also remains scarce.…”
Section: Mobilise Increase and Focus Funding And International Techni...mentioning
confidence: 99%
“…Pollution has until recently been overlooked in international development planning and largely neglected in the global health agenda [ 25 ]. For too long, pollution has been regarded as the unavoidable price of economic progress [ 25 ], a view that arose out of the experience of the 19th and 20th centuries when combustion of fossil fuels – coal in particular – was the engine of economic growth and pollution was seen as unavoidable. Today, however, the claim that pollution is inevitable and that pollution control costs jobs and stifles economies is no longer tenable.…”
Section: Introductionmentioning
confidence: 99%
“…Today, however, the claim that pollution is inevitable and that pollution control costs jobs and stifles economies is no longer tenable. It has been disproven by the experience of the many countries that have more than doubled their GDPs in the past half century while greatly reducing pollution [ 24 25 26 ]. It has become irrelevant with the increasing availability of low-cost, renewable sources of energy and advances in green chemistry.…”
Section: Introductionmentioning
confidence: 99%